Pattern of Coronary Artery Involvement in Patients Undergoing Coronary Angiography at Cardiac Center in Western Nepal - KC, Bishal; Gautam, Samir; Dhungel, Sachin; Hirachan, Anish; Shakya, Abhishesh; Khan, Mazhar; Panjiyar, Rajesh; Thapa, Kristi; Nepali, Ram (Nepalese Heart Journal, 2025)
Background and purpose: Around the globe coronary artery disease (CAD) is the most prevalent cause of death which requires effective diagnosis and management. Coronary angiography (CAG) is the most trusted method for the diagnosis. This study aims to identify the indications, findings, and associated risk factors among the patients undergoing CAG and its correlation to gender and ethnicity. Methods: The research involved a retrospective study of patients who underwent CAG from September 2017 to September 2023. Result: A total of 2335 individuals were included in the study. The mean age was 58.99±11.60years. Male were 1463(62.7%) and females were 872(37.3%). The most common indication for CAG was acute coronary syndrome (ACS) 1270(54.8%) more common among males 860(67.24%). The most common arterial access was radial artery 2000(85.7%). Obstructive coronary artery disease was the most common finding, seen in 1,794 cases (76.8%), with a higher prevalence among males (1,202 cases, 67%). It was also more frequent among Muslims (84.3%), Terai/Madhesi (82.4%), and Dalits (82.3%). Multivessel involvement was the most common pattern, found in 1,060 cases (45.4%). It was more frequent in males (713 cases, 67.26%) and showed higher prevalence among Muslims (56.9%), Terai/Madhesi (53.2%), and Dalit groups (48.7%). The single vessel, double-vessel, and triple-vessel diseases were 734(40.91%), 516(28.76%), and 544(30.32%) respectively. The left main coronary artery disease was involved in 95(4.1%). Hypertension stood as the leading risk factor present in 903(38.7%) followed by Diabetes Mellitus in 714(30.6%) and Smoking in 563(24.1%). Conclusion: The high prevalence of obstructive coronary artery disease and multivessel involvement, particularly among males, and individuals from the Terai/Madhesi, Dalit, and Muslim communities, underscores the need for targeted screening and early intervention strategies in these high-risk groups. Clinicians should maintain a high index of suspicion and prioritize timely diagnostic evaluation in these populations to improve outcomes and reduce cardiovascular burden.